ARDUINO-BASED AUTOMATIC CONTROL SYSTEM APPLICATION FOR DROPLET COMBUSTION HEATER DRIVE - Issafira, Radissa Dzaky; Tasya, Nellysa Arviana; Rizqullah, Andre Rifqi; Hafizh, Rakha Abyan; Soegianto, Verio Rinaldo (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
The droplet test in combustion is a widely used method for evaluating the physical properties of fuels, such as biodiesel. This examination entails depositing liquid droplets onto a surface and monitoring their properties. This study employs a semi-automatic control system in droplet testing to enhance the accuracy and efficiency of the process. The Arduino sensor system controls the heater-connected screwdriver by the droplet temperature. One button activates the Arduino sensor system to switch on and move the heater toward the droplet location. After the droplet turn into flame and shows its light intensity, the sensor captures the signals and the heater automatically reverses to maintain flame temperature. The comparison between droplet temperatures taken using manual and automatic methods were compared with 10 repetitions for each experiment. The results showed that automatic method has higher accuray result with average coefficient variation value of 4-9%, whereas the manual is 9-48%. This method is anticipated to improve the precision and efficacy of droplet testing to a fully automated control system.